Exploration of the Mechanism of Intimal Hyperplasia in Autogenous Arteriovenous Fistula - Liang, Yuxin; Zhao, Yanlong (Journal of Contemporary Medical Practice, 2025)
Objective: To explore the mechanism of intimal hyperplasia (IH) in autogenous arteriovenous fistula (AVF) from the perspective of integrated traditional Chinese and western medicine. Methods: This study reviewed the relevant literature, analyzed and summarized the mechanism of intimal hyperplasia of autogenous arteriovenous fistula from the perspective of integrated traditional Chinese and western medicine. Conclusion: Intimal hyperplasia of autogenous arteriovenous fistula involves many aspects. From any Angle, it provides a theoretical basis for clinical research and further guides clinical practice.